A Successful Approach to the Bibliography of Literature on the History of the Ancient Cities of Uzbekistan (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article analyzes the inclusion of literature on urban development, economy, culture, science, art, historical topography in the sections of the bibliographic guide on the history of the city of Khiva in Uzbekistan. The importance of creating a bibliography of literature on the history of urban development of Khiva from ancient times to the present has been revealed to all readers.